2018
DOI: 10.3389/fpls.2018.01846
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Mechanisms Behind the Metabolism of 2,4,6-Trinitrotoluene by Glutathione Transferases U25 and U24 That Lead to Alternate Product Distribution

Abstract: The explosive xenobiotic 2,4,6-trinitrotoluene (TNT) is a major worldwide environmental pollutant and its persistence in the environment presents health and environmental concerns. The chemical structure of TNT dictates that biological detoxification pathways follow predominantly reductive transformation of the nitro groups, and as a result, TNT is notoriously recalcitrant to mineralization in the environment. Plant-based technologies to remediate this toxic pollutant rely on a solid understanding of the bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The main cis-regulatory elements found in the 5' up-regulatory region of the genes are rather different, although both genes contain several presumably abiotic stress-and hormone-inducible sequences (Table S2). The AtGSTU19 represents a significant percentage of the GST pool in Arabidopsis [26], while AtGSTU24 came to the forefront especially according to its detoxification ability [9,45]. Both isoenzymes may have a role in salt stress responses and possess high activity toward the CDNB substrate [5,11,46].…”
Section: Arabidopsis Plants Compensated For the Decreased Atgstu Tranmentioning
confidence: 99%
“…The main cis-regulatory elements found in the 5' up-regulatory region of the genes are rather different, although both genes contain several presumably abiotic stress-and hormone-inducible sequences (Table S2). The AtGSTU19 represents a significant percentage of the GST pool in Arabidopsis [26], while AtGSTU24 came to the forefront especially according to its detoxification ability [9,45]. Both isoenzymes may have a role in salt stress responses and possess high activity toward the CDNB substrate [5,11,46].…”
Section: Arabidopsis Plants Compensated For the Decreased Atgstu Tranmentioning
confidence: 99%
“…In conclusion, the possible mechanism of Meisenheimer–dihydride complexes of TNT from the metabolism of several flavoprotein reductases (or microorganisms) is fully explored in detail. 28 It is of great significance for the design and development of new technologies that can fully degrade the nitro aromatic explosives.…”
Section: Discussionmentioning
confidence: 99%
“…Tzafestas et al [64] found that GSTU24 and GSTU25 genes in A. thaliana can catalyze glutathione coupling with 2,4,6-trinitrotoluene (TNT). These results indicate that glutathione s-transferase can directly or indirectly bind to pollutants, thereby reducing the damage that pollutants induce in plants.…”
Section: Gst Activity Towards Guanidine Thiocyanate In Vitromentioning
confidence: 99%